Intoxicated children at an intensive care unit: popular medicine risks, complications and costs. (Colombia Medica, 2009)
Introduction: The Hospital Universitario del Valle (HUV) at the Pediatrics Intensive Care Unit (PICU) admits intoxicated patients, erroneously medicated by «teguas» or family members with serious aggravation of basic diseases or generating severe intoxications. Absent reports of these practices in Colombia motivated the publication of this case series Objective: To report a series of pediatric intoxication cases secondary to oral or dermatological application of varied substances by healers («teguas») or family members, leading to admission at the PICU, and to describe complications and hospital costs of these events. Methodology: Clinical charts of patients admitted to the PICU with diagnosis of exogenous intoxication during May 2001 to September 2004, were reviewed. Of 28 registered cases during that time, only 14 clinical charts were recovered. Variables evaluated included: age, gender, proceeding, administered substance, person responsible for the administration, complications, days of mechanical ventilation, total days at the intensive care unit and average costs. Of the 14 medical records with exogenous intoxications only 5 cases were involuntary and 9 were related to the administration of substances by quacks or family members; these are the ones reported in this series. Results: We report a total of 9 intoxicated patients, 5 girls and 4 boys, with an age range from 1 to 24 months, all from Cali. Topical administered substances: alcohol 6/9, vinegar 1/9; oral: aspirin 2/9, paico 1/9, and unidentified herbs 1/9. Administered substances by teguas: 6 patients; 3 by family members. All patients had metabolic acidosis with an increased anion gap: 27 in average (range from 21 to 32). All required mechanical ventilation (2 to 32 day range). Average hospital day costs were $6’657,800 pesos (around U$3,000.oo). Three patients died and 4 presented acute renal failure, 2 convulsions, 2 nosocomial infections, 1 subglotic stenosis. Conclusions and recommendations: Those practices are a high risk for children and have high health costs. Mortality and severe complications are high. Educational campaigns should be started in the community to prevent these cases.